Citation Practices at the International Court: The Situation in Darfur, Sudan - Manley, Stewart (Cambridge University Press, 2017)
This article analyzes the 9,203 citations made by the International Criminal Court (ICC) in its cases involving Sudan. To date, few empirical studies have assessed the citation practices of courts and even fewer of international courts. The data is rich. It reveals, for instance, the changing nature of the Court’s citations over time,the disproportionate distribution of citations among chambers, the potential impact of party pleadings on citations, and the allocation of citations to previous rulings of the Court, other international tribunals and domestic courts. The article also explores possible explanations for the patterns that emerge and assesses what the patterns may mean for the Court.Unlike most other citation analyses, the study provides the additional benefit of having categorized the citations based on their function, distinguishing for instance between citations that the Court uses to help it decide legal and factual issues, and those it does not.